2017
DOI: 10.4236/ajibm.2017.78069
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating China’s Oil Security and Overseas Oil Investment

Abstract: Oil security is the major concern of China's energy policy due to the no effective substitute nature of oil and the heavy reliance on internationally imported crude oil. In this paper, a synthesized indicator system was established to analyze China's oil security from four aspects and Chinese government's oil security policies were also discussed. From this analysis, we concluded that the main risk in China's oil security was the gaps between domestic oil supply and demand, and the main means that Chinese gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In this case, the profits pursuit behavior of the NOCs not only brings market benefits for the oil companies, but also increases and diversifies China's oil supply. Meanwhile, it is demonstrated that China's overseas oil investments contribute to China's oil import both through the increase of oil import volume and the diversification of import sources, and thus enhancing China's oil security (Zheng, 2017;Duan et al, 2018;Shi & Cai, 2020;Zhao et al, 2020). Notably, in normal times, most of the NOCs' overseas equity oil and crude oil production will not be shipped back to China.…”
Section: The Hedging Mechanism For Oil Securitymentioning
confidence: 99%
“…In this case, the profits pursuit behavior of the NOCs not only brings market benefits for the oil companies, but also increases and diversifies China's oil supply. Meanwhile, it is demonstrated that China's overseas oil investments contribute to China's oil import both through the increase of oil import volume and the diversification of import sources, and thus enhancing China's oil security (Zheng, 2017;Duan et al, 2018;Shi & Cai, 2020;Zhao et al, 2020). Notably, in normal times, most of the NOCs' overseas equity oil and crude oil production will not be shipped back to China.…”
Section: The Hedging Mechanism For Oil Securitymentioning
confidence: 99%
“…There are some other factors of global energy trade which include buyer, seller, policy maker and service providers. These factors should be considered for global Zheng [24] analyzed the uncertainties on investment and prices of natural gas fuel for a competitive market and conclude that energy business has a great potential in the global market. Liedtke [25] also mentioned that the oil investment decision of China is favorable for OBOR partner countries.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…The major part of China's energy security plan is to access to sufficient oil supplies which are also a part of China's national security [24]. More than 11 million barrels per day oil is the requirement for consumption in China which leads China to become atop most oil importer in [45].…”
Section: Chinese Oil Gas and Energy Supply Chain In Obor Contextmentioning
confidence: 99%
See 2 more Smart Citations